Establishment of normative ranges of the healthy human immune system with comprehensive polychromatic flow cytometry profiling - Yi, John S.; Rosa-Bray, Marilyn; Staats, Janet; Zakroysky, Pearl; Chan, Cliburn; Russo, Melissa A.; Dumbauld, Chelsae; White, Scott; Gierman, Todd; Weinhold, Kent J.; Guptill, Jeffrey T. (PloS one, 2019)
Existing normative flow cytometry data have several limitations including small sample sizes, incompletely described study populations, variable flow cytometry methodology, and limited depth for defining lymphocyte subpopulations. To overcome these issues, we defined high-dimensional flow cytometry reference ranges for the healthy human immune system using Human Immunology Project Consortium methodologies after carefully screening 127 subjects deemed healthy through clinical and laboratory testing. We enrolled subjects in the following age cohorts: 18-29 years, 30-39, 40-49, and 50-66 and enrolled cohorts to ensure an even gender distribution and at least 30% non-Caucasians. From peripheral blood mononuclear cells, flow cytometry reference ranges were defined for >50 immune subsets including T-cell (activation, maturation, T follicular helper and regulatory T cell), B-cell, and innate cells. We also developed a web tool for visualization of the dataset and download of raw data. This dataset provides the immunology community with a resource to compare and extract data from rigorously characterized healthy subjects across age groups, gender and race.